Impact of Glaucoma on Quality of Life and Activities of Daily Living. Issue 1 (June 2015) - Park, Sangshin; Kho, Young Lim; Kim, Hyo-Jin; Kim, JiHyun; Lee, Eun-Hee
Objective/Background: This study was performed to assess the associations of glaucoma with health-related quality of life (HRQOL) and activities of daily living (ADL). Methods: Using data from the Korean National Health and Nutrition Examination Survey III in 2005, we analysed 9, 047 participants (≥ 50 years old) and 3, 518 participants (> 65 years old) to assess the associations of glaucoma with HRQOL and ADL, respectively. The diagnosis of glaucoma was based on questionnaires. HRQOL was evaluated by the EuroQol five-dimension descriptive system (EQ-5D) and the EuroQol visual analogue scale. The ADL was evaluated by the Korean-optimised ADL questionnaire. Logistic-regression analyses were used to assess the associations of glaucoma with HRQOL and ADL. Results: The glaucoma patients showed lower HRQOL and ADL scores compared to the healthy participants. The glaucoma patients showed significantly higher prevalence of impaired health status in all dimensions of EQ-5D, as well as in the "bathing" dimension of ADL as compared with the healthy participants. Impaired HRQOL and ADL were significantly associated with the risk of glaucomatous status (odds ratio [95% confidence interval] of EQ-5D: 1.65 [1.33, 2.05], EuroQol visual analogue scale: 1.75 [1.43, 2.15], and ADL: 2.04 [1.12, 3.74]). Conclusion: In line with previous studies conducted in other countries, Koreans with glaucoma had impaired HRQOL and ADL as compared with healthy Koreans.